Resiko Karies Gigi dari Konsumsi Makanan Kariogenik pada Anak Sekolah Dasar - Widyastuti, Nugraheni; Jumriani; Wahyudadi, Badai Septa (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Dental and oral health problems in Indonesia have increased based on the results of the 2007 Basic Health Research by 43.4% to 53.3% in 2013 and by 57.6% in 2018. The prevalence of caries in South Sulawesi is 55.54%, in Makassar City by 52.09%, and in the 5-9 year age group by 65.51%. Dental caries often occurs in children because they tend to like sweet foods and drinks and do not clean them. Caries in children can be influenced by factors such as poor eating habits, tooth brushing habits, and rarely checking with a dentist. School-age children usually like sweet foods, such as candy, chocolate, and cakes. These sweet foods are high in carbohydrates which are prone to causing caries. Caries if left untreated can have a negative impact on the quality of life of children both physically and psychologically, from adolescence to adulthood. The effects of caries can cause periodontal disease, which is a severe infection of the gums and bones that support the teeth. The purpose of this study was to determine the analysis of the risk of dental caries based on the consumption of cariogenic foods in elementary school children. This research method uses a survey with a cross-sectional approach, starting from measuring caries using direct examination with a status card and children's consumption habits using a questionnaire. Data were tested using anova and chi-square. The results showed that the incidence of dental caries based on the consumption of cariogenic foods was most commonly found, namely moderate caries rates and moderate cariogenic food consumption of 14 people (28%). The conclusion is that there is a relationship between cariogenic food consumption and the risk of dental caries. Keywords: Risk of dental caries; cariogenic foods